Decoy oligonucleotides targeting NF-κB: a promising therapeutic approach for inflammatory diseases - Maryam Mahjoubin-Tehran; Samaneh Rezaei; Alexandra E. Butler; Amirhossein Sahebkar (Inflammation Research, 2025)

Statins and adhesion molecules: a review of a novel pleiotropic property of statins - Mahvash Sadeghi; Sajad Dehnavi; Sanaz Keshavarz Shahbaz; Khadijeh Koushki; Alexandra E. Butler; Tannaz Jamialahmadi; Amirhossein Sahebkar (Immunologic Research, 2025)

Regulatory effect of curcumin on CD40:CD40L interaction and therapeutic implications - Fatemeh Askarizadeh; Alexandra E. Butler; Prashant Kesharwani; Amirhossein Sahebkar (Food and Chemical Toxicology, 2025)

TLR/NLRP3 inflammasome signaling pathways as a main target in frailty, cachexia and sarcopenia - Sanaz Keshavarz Shahbaz; Aida Mokhlesi; Roghaye Keshavarz Sadegh; Kimia Rahimi; Tannaz Jamialahmadi; Alexandra E. Butler; Prashant Kesharwani; Amirhossein Sahebkar (Tissue and Cell, 2025)

Targeting mTOR with curcumin: therapeutic implications for complex diseases - Danial Khayatan; Seyed Mehrad Razavi; Zahra Najafi Arab; Hadis Nasoori; Abtin Fouladi; Aytak Vahdat Khajeh Pasha; Alexandra E. Butler; Sercan Karav; Saeideh Momtaz; Amir Hossein Abdolghaffari; Amirhossein Sahebkar (Inflammopharmacology, 2025)

The analgesic effect of curcumin and nano-curcumin in clinical and preclinical studies: a systematic review and meta-analysis - Pooya Hajimirzaei; Hossein Eyni; Maryam Razmgir; Sajad Abolfazli; Simin Pirzadeh; Faeze Sadat Ahmadi Tabatabaei; Ayda Vasigh; Nafiseh Yazdanian; Fatemeh Ramezani; Atousa Janzadeh; Alexandra E. Butler; Amirhossein Sahebkar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Curcumin and Ferroptosis: a Promising Target for Disease Prevention and Treatment - Zahra Foroutan; Alexandra E. Butler; Gokhan Zengin; Amirhossein Sahebkar (Cell Biochemistry and Biophysics, 2024)

Relationship between endocrine disrupting chemicals (phthalate metabolites, triclosan and bisphenols) and vitamin D in female subjects: An exploratory pilot study - Edwina Brennan; Alexandra E. Butler; Manjula Nandakumar; Kristie Thompson; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2024)

Association of flame retardants, polybrominated diethyl ethers (PBDEs), with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2023)

Impact of curcumin on p38 MAPK: therapeutic implications - Hedieh Sadat Shamsnia; Mahtab Roustaei; Danial Ahmadvand; Alexandra E. Butler; Dorsa Amirlou; Sanam Soltani; Saeideh Momtaz; Tannaz Jamialahmadi; Amir Hossein Abdolghaffari; Amirhossein Sahebkar (Inflammopharmacology, 2023)

Association of polychlorinated biphenyls with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Environmental Research, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Expression and localization of transient receptor potential channels in the bovine uterus epithelium throughout the estrous cycle - Maryam Ghavideldarestani; Alexandra E. Butler; Sadegh Shirian; Stephen L. Atkin (Molecular Biology Reports, 2019)

Cortical and thalamic connectivity to the second auditory cortex of the cat is resilient to the onset of deafness - Blake E. Butler; Alexandra de la Rua; Taylor Ward-Able; Stephen G. Lomber (Brain Structure and Function, 2018)

Relationship between pancreatic vesicular monoamine transporter 2 (VMAT2) and insulin expression in human pancreas - Yoshifumi Saisho; Paul E. Harris; Alexandra E. Butler; Ryan Galasso; Tatyana Gurlo; Robert A. Rizza; Peter C. Butler (Journal of Molecular Histology, 2008)